Hybrid Federated Social Networking Sites for eLearning - Beauty Mugoniwa; Enerst Ketcha Ngassam; Shawren Singh (Politeknik Negeri Batam, 2026)
This study explores the feasibility and development of hybrid federated social networking site (HFSNS) architecture for enhancing teaching and learning activities in higher education. The study addresses the increasing limitations of centralised social networking sites. The main objective is to develop an HFSNS architecture that can support scalability, interoperability and privacy-preserving educational collaborations across SNS platforms. The research is grounded in design science research (DSR), while Dubin’s theory building methodology guides the systematic identification and construction of architectural components and their attributes. The study pursued a mixed-method research design, based on a pragmatist philosophy, which therefore provided a basis for an exploratory case study of one university. Forty-five respondents were purposively selected for unstructured interviews, while 748 contributed to an online survey. Qualitative data were analysed thematically and quantitative data was analysed using regression and correlation statistical to examine the relationships between HFSNS adoption and perceived eLearning opportunities. Findings indicate high institutional readiness for HFSNS adoption, since most participants are already using SNSs for teaching and learning activities. Statistical results shows a significant relationship between HFSNS implementation and improved eLearning opportunities, platform independence, privacy protection, improved collaboration and timely academic feedback. However, limitations such as interoperability and infrastructural challenges were also identified. The study proposes a novel HFSNS for eLearning and it extends DSR in education by integrating federated social networking (FSN) principles with eLearning systems. This study also brings in empirical evidence on the readiness and opportunities of FSN in higher education.